Barriers to Living Donor Kidney Transplantation among Black or Older Transplant Candidates - Weng, Francis L. (American Society of Nephrology, 2010)
Background and objectives: Lower rates of living donor kidney transplant (LDKT) among transplant candidates who are black or older may stem from lower likelihoods of (1) recruiting potential living donors or (2) potential donors actually donating (donor “conversion”). Design, setting, participants, & measurements: A single-center, retrospective cohort study was performed to determine race, age, and gender differences in LDKT, donor recruitment, and donor conversion. Results: Of 1617 kidney transplant candidates, 791 (48.9%) recruited at least one potential living donor, and 452 (28.0%) received LDKTs. Black transplant candidates, versus non-blacks, were less likely to receive LDKTs (20.5% versus 30.6%, relative risk [RR] = 0.67), recruit potential living donors (43.9% versus 50.7%, RR = 0.86), and receive LDKTs if they had potential donors (46.8% versus 60.3%, RR = 0.78). Transplant candidates ≥60 years, versus candidates 18 to <40 years old, were less likely to receive LDKTs (15.1% versus 43.2%, RR = 0.35), recruit potential living donors (34.0% versus 64.6%, RR = 0.53), and receive LDKTs if they had potential donors (44.5% versus 66.8%, RR = 0.67). LDKT and donor recruitment did not differ by gender. Race and age differences persisted in multivariable logistic regression models. Among 339 candidates who recruited potential donors but did not receive LDKTs, blacks (versus non-blacks) were more likely to have potential donors who failed to donate because of a donor-related reason (86.9% versus 72.5%). Conclusions: Black or older kidney transplant candidates were less likely to receive LDKTs because of lower likelihoods of donor recruitment and donor conversion.